Influence of roughness on lubrication characteristics of high-speed helical gears in aviation engines - HOU Yankun; LIU Zhengang; HU Dunke; GUO Hailong; LIU Zhenxia (Xibei Gongye Daxue Xuebao)
This study investigates the lubrication characteristics of a certain type of high-speed helical gear in aviation engines. Employing a thermo-elastohydrodynamic lubrication model based on finite line contact, it considers the influence of helical gear surface roughness at the meshing position. Findings reveal patterns in how roughness wavelength, amplitude, and dimensionless parameters (material parameter G, speed parameter U, load parameter W) affect lubrication. By introducing the standard deviation of oil film characteristic parameter fluctuations (pressure, thickness, temperature rise), the extent to which different input parameters impact film stability is quantified. Results show that gear surface roughness significantly destabilizes the lubricant film. With roughness on the same order as the film thickness, fluctuations of oil film parameters can reach 50% relative to the smooth case, significantly reducing local film thickness in the contact region compared to the central area and increasing the risk of dry friction. Increases in roughness amplitude and decreases in wavelength exacerbate fluctuations, while roughness distribution in the gear rolling direction more significantly affects lubricant flow. With rising G, oil film pressure and temperature fluctuations intensify, while increasing U suppresses pressure fluctuations caused by roughness to some extent. Greater W magnifies the impact of roughness. Improving lubrication conditions for helical gears can be achieved by minimizing surface roughness peaks and avoiding dense distributions of sharp roughness spikes.